Analyse the relationship carbon monoxide status with development in Kuantan, Pahang - Zaidatul Syahida, Adnan (2016)
In Malaysia, industrialization, urbanization, and rapid traffic growth have contributed significantly to economic growth. Pockets of heavy pollution are being created by emissions of smoke from major industrial zones, a dramatic increase in the number of residences, office buildings, manufacturing industries, increase in number of motor vehicles and trans – boundary pollution based on previous study. This study focused on relationship between carbon monoxide statuses with development in Kuantan, Pahang. The satellite-based carbon monoxide status for the period investigated obtained from public domain.Meanwhile, development status of study area was analysed based on satellite images provided by Google Satellite Pro application.The carbon monoxide status over correspondent development area wasretrieved using geographical information system technique.From statistical analysis, theareas that are developed with industryshows correlation (r = 0.562) better than settlements (urban) (r = 0.460).As conclusion, the relationship between carbon monoxide emissions and development at study area has positive correlation with each other.Thus, this study can be used as a guideline to local authority in managing and planning for future development.